Variability of kinetic variables during gait in unilateral transtibial amputees - Svoboda, Zdenek; Janura, Miroslav; Cabell, Lee; Elfmark, Milan (Prosthetics and orthotics international, 2012)
BACKGROUND: Prosthetic gait increases demands on stability. Some variability measures can be used to investigate the stability of movement for prosthetic feet. OBJECTIVES: The purpose of this study was to determine the influence of the prosthetic foot on ground reaction force variability for transtibial amputee gait. STUDY DESIGN: Comparative analysis. METHODS: Eleven male unilateral transtibial amputees participated in this study. Each subject walked at self-selected speed with both conventional (SACH) and energy storing (Sureflex) feet. Time and ground reaction force variables and their coefficients of variation were calculated for each foot type and limb. RESULTS: Mediolateral force variables had high variability for all conditions. The Sureflex had a larger variability than the SACH foot for the braking peak (p < 0.05), which may have been caused by gait instability after the heel strike. There were significant differences between intact and prosthetic limbs in total loading (force impulses) with the SACH foot (p < 0.05). CONCLUSIONS: The prosthetic foot and alignment issues related to the foot influence GRF variability. During the braking phase the SACH foot is characterized by higher variability in mediolateral direction and Sureflex by higher variability in anterior-posterior direction. CLINICAL RELEVANCE: Differences in variability in ground reaction force variables can represent a person's stability. Observing variability can contribute to better understanding of critical events in gait cycle with the use of various prosthetic feet.
Keywords: pata; dospělí; Movement; umělé končetiny; Prosthesis Design; pohyb; Weight-Bearing; Adult; Gait; protézy - design; zatížení muskuloskeletálního systému; lidé; Tibia; Heel; Postural Balance; biomechanika; Male; Amputees; amputovaní; tibie; lidé středního věku; mužské pohlaví; Artificial Limbs; chůze (způsob); Middle Aged; Biomechanical Phenomena; posturální rovnováha; Humans